Work stress, mental health, and employee performance - Chen, Biao; Wang, Lu; Li, Biao; Liu, Weixing (Frontiers in Psychology, 2022)
The COVID-19 pandemic outbreak—as a typical emergency event—significantly impacts employees’ psychological status and, thus, negatively affects their performance. Hence, along with focusing on the mechanisms and solutions to alleviate work stress’ impact on employee performance, we also examine the relationship between work stress, mental health, and employee performance. Further, we analyzed the moderating role of servant leadership in the relationship between work stress and mental health, but the result was not significant. The results contribute to providing practical guidance for enterprises to improve employee performance in the context of major emergencies.